2018
DOI: 10.24843/lkjiti.2018.v09.i03.p08
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality Reduction using PCA and K-Means Clustering for Breast Cancer Prediction

Abstract: Breast cancer is the most important cause of death among women. A prediction of breast cancer in early stage provides a greater possibility of its cure. It needs a breast cancer prediction tool that can classify a breast tumor whether it was a harmful malignant tumor or un-harmful benign tumor. In this paper, two algorithms of machine learning, namely Support Vector Machine and Extreme Gradient Boosting technique will be compared for classification purpose. Prior to the classification, the number of data attri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 13 publications
(12 reference statements)
0
22
0
5
Order By: Relevance
“…Through the experimental results, it has been shown that the random selection of RF-PCA provides better accuracy than other methods. Additionally, Jamal et al in [76] focused on the number of features for the classification of breast cancer from the original White Blood Cell (WBC) data set can be reduced by the feature extracting. The metric measurement results that the dimensionality reduction using the K-means cluster is almost as good as PCA.…”
Section: Review For Pca Algorithmmentioning
confidence: 99%
“…Through the experimental results, it has been shown that the random selection of RF-PCA provides better accuracy than other methods. Additionally, Jamal et al in [76] focused on the number of features for the classification of breast cancer from the original White Blood Cell (WBC) data set can be reduced by the feature extracting. The metric measurement results that the dimensionality reduction using the K-means cluster is almost as good as PCA.…”
Section: Review For Pca Algorithmmentioning
confidence: 99%
“…Optimum , paremetrelerinin tespiti için . gizli ünitenin aktivasyonu (2) (1) , (1) değerleri ise giriş ile gizli katman arasındaki yani kodlayıcı olarak adlandırılan kısımdaki ağın ağırlık parametreleridir. Denklem 9'da oto-kodlayıcının toplam maliyet fonksiyonu gösterilmiştir.…”
Section: Kullanilan Boyut Küçültme Yöntemleri̇unclassified
“…analizi birçok alanı kapsamaktadır. Veri Bu çalışmada, doğrusal boyut azaltma tekniklerinden PCA [1], [2], LDA [3], [4] ve doğrusal olmayan boyut azaltma tekniklerinden Autoencoder yöntemleri incelenmiştir [5], [6]. Bu yöntemlerin performansları, literatürde sık kullanılan MNIST [7] veri kümesi (el yazısıyla yazılmış rakamlar) kullanılarak elde edilmiş, sınıflandırma doğrulukları ve hesaplama süreleri kıyaslanmıştır.…”
Section: Introductionunclassified
“…The experiment was performed using the Wisconsin dataset, while the result showed that KNN outperforms Naïve Bayes with the higher accuracy of 97.51% compared to that of 96.19%. Another breast cancer prediction work has been reported in Jamal et al ( 2018 ), in which authors utilized the hybrid technique of Extreme Gradient Boosting technique and Support Vector Machine. Furthermore, they also applied the Principle Component Analysis (PCA) and K-Means Clustering method to reduce the problem dimensionality.…”
Section: Introductionmentioning
confidence: 99%